The Transgender Exigency Defining Sex and Gender in the 21st Century - Schiappa, Edward (Taylor & Francis, 2022)
At no other point in human history have the definitions of "woman" and "man," "male" and "female," "masculine" and "feminine," been more contentious than now. This book advances a pragmatic approach to the act of defining that acknowledges the important ethical dimensions of our definitional practices. Increased transgender rights and visibility has been met with increased opposition, controversy, and even violence. Who should have the power to define the meanings of sex and gender? What values and interests are advanced by competing definitions? Should an all-boys' college or high school allow transgender boys to apply? Should transgender women be allowed to use the women's bathroom? How has growing recognition of intersex conditions challenged our definitions of sex/gender? In this timely intervention, Edward Schiappa examines the key sites of debate including schools, bathrooms, the military, sports, prisons, and feminism, drawing attention to the political, practical, and ethical dimensions of the act of defining itself. This is an important text for students and scholars in gender studies, philosophy, communication, and sociology.